Making Charcoal from Nipah (Nypa fruticans) Frond Waste as an Adsorbent to Extend the Shelf Life of Fresh Bread - Nur Sabila, Ayu; Rahayu, Theresia Evila Purwanti Sri; Prasadi, Oto (Jurnal Teknik Kimia dan Lingkungan, 2023)
Fresh bread has high potential for creating food waste that increases every year, because of its relatively short shelf life of 3-4 days after leaving the baking process. One way to extend the shelf life of bread is by using charcoal. Nipah fronds contain lignin elements that are good for charcoal. This study aims to determine the characteristics of charcoal from nipah fronds, the effectiveness of charcoal's ability to extend the shelf life of fresh bread, the effect of burning time, particle size and adsorbent mass on the storage time of fresh bread, the effect of the ratio of nipah frond adsorbent to commercial silica gel on the storage time compared to quality requirements of fresh bread of SNI 01-3840-1995 2013. Charcoal characterization includes quality tests based on SNI No. 06-3730-1995 on technical charcoal, namely water content and iodine absorption parameters and also Scanning Electron Microscopy (SEM) test. Based on the results of the study, charcoal from nipah frond waste has characteristics of water content that have met the quality standards of SNI 06-3730-1995 and in iodine absorbency only samples with pyrolysis time of 4 hours that have met the quality standards of SNI 06-3730-1995. Giving variations in charcoal burning time, mass and particle size of adsorbent powder affects the shelf life and quality requirements of fresh bread. Adsorbent packaging using teabags and silica gel paper can extend the shelf life of fresh bread up to 27 hours compared to those without adsorbent.